Effectiveness of acupuncture for cancer pain: protocol for an umbrella review and meta-analyses of controlled trials. Issue 12 (10th December 2017) - He, Yihan; Liu, Yihong; May, Brian H; Zhang, Anthony Lin; Zhang, Haibo; Lu, ChuanJian; Yang, Lihong; Guo, Xinfeng; Xue, Charlie Changli
Abstract : Introduction : The National Comprehensive Cancer Network guidelines for adult cancer pain indicate that acupuncture and related therapies may be valuable additions to pharmacological interventions for pain management. Of the systematic reviews related to this topic, some concluded that acupuncture was promising for alleviating cancer pain, while others argued that the evidence was insufficient to support its effectiveness. Methods and analysis: This review will consist of three components: (1) synthesis of findings from existing systematic reviews; (2) updated meta-analyses of randomised clinical trials and (3) analyses of results of other types of clinical studies. We will search six English and four Chinese biomedical databases, dissertations and grey literature to identify systematic reviews and primary clinical studies. Two reviewers will screen results of the literature searches independently to identify included reviews and studies. Data from included articles will be abstracted for assessment, analysis and summary. Two assessors will appraise the quality of systematic reviews using Assessment of Multiple Systematic Reviews; assess the randomised controlled trials using the Cochrane Collaboration's risk of bias tool and other types of studies according to the Newcastle-Ottawa Scale. We will use 'summary of evidence' tables to present evidence from existing systematic reviews and meta-analyses. Using the primary clinical studies, we will conduct meta-analysis for each outcome, by grouping studies based on the type of acupuncture, the comparator and the specific type of pain. Sensitivity analyses are planned according to clinical factors, acupuncture method, methodological characteristics and presence of statistical heterogeneity as applicable. For the non-randomised studies, we will tabulate the characteristics, outcome measures and the reported results of each study. Consistencies and inconsistencies in evidence will be investigated and discussed. Finally, we will use the Grading of Recommendations Assessment, Development and Evaluation approach to evaluate the quality of the overall evidence. Ethics and dissemination: There are no ethical considerations associated with this review. The findings will be disseminated in peer-reviewed journals or conference presentations. PROSPERO registration number: CRD42017064113.